PENGARUH PENGETAHUAN INVESTASI, LITERASI KEUANGAN, MOTIVASI INVESTASI PADA MINAT INVESTASI KARYAWAN - ningrum, Saskia fitria; Wibowo, Purwo Adi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
This research aimed to examine the influence of investment knowledge, financial literacy, and investment motivation on investment interest in CV Aulia Jati Furniture employees in Jepara. The research population was 118 employees of CV Aulia Jati Furniture, of which all sample members were taken as samples (saturated sampling). The required primary data were collected by questionnaire and then analyzed by multiple linear regression using SPSS 26. The results showed that investment knowledge and investment motivation had a significant positive effect on investment interest while financial literacy had no effect.